PSYCHOLOGICAL ASPECTS OF LEADERSHIP QUALITY FORMATION IN PROFESSIONAL TRAINING OF FUTURE LEADING OFFICERS - Zarychanskyi, O.; Holub, O. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2021)
The article considers leadership as an internal state of personality, which is aimed at success, deeply motivated, leads an active life, confident in their decisions and actions. It is established that the leader provides the functions of integration and purposefulness of the team and acts on the principle of direct participation in its life. The need to take into account the peculiarities of the social environment, the specifics of professional activity and the challenges facing the specialist is substantiated in the question of formulation of leadership qualities. Thus, the use of case technology makes it possible to significantly strengthen the system of training officer leaders by integrating theoretical training with professional and practical and research activities, the use of appropriate content (leadership experience), interactive development of professionally important leadership qualities for military leaders. Purposeful formation of leadership qualities in the process of professional training of cadets of higher education institutions (higher military educational institutions) not only ensures the successful exercise of power, but also becomes the basis of socio-psychological impact on the environment and servicemen in the future. It is proved that the process of formation of leadership qualities in cadets of higher education institutions is defined as a set of pedagogical situations that contribute not only to the successful development of leadership qualities, but also to the general self-improvement of the individual. Understanding of scientific sources allows us to state that the leadership qualities of the personality of the future officer-leader are the traits that provide the ability to stand out in a particular case and make responsible decisions in significant situations; use innovative approaches to solve the problem; successfully influence followers to achieve common goals; to create a favourable sociopsychological climate in the military.